Electrospun biodegradable nanofibers loaded with epigallocatechin gallate for guided bone regeneration. (1st June 2022) - Song, Liang; Xie, Xianrui; Lv, Cuiting; Khan, Atta ur Rehman; Sun, Yang; Li, Ruixue; Yao, Juan; EL-Newehy, Mohamed; EL-Hamshary, Hany; Morsi, Yosry; Mo, Xiumei; Yu, Youcheng
Abstract: Guided bone regeneration through biomaterial-based formulations can prevent soft tissue migration into the bone defect area through a barrier membrane. However, bone regeneration requires bioactive external interference. Here, we report a biodegradable electrospun poly-l -lactic acid/gelatin-based nanofibrous membrane encapsulating epigallocatechin gallate (EGCG) within the core, with a smooth profile, desirable physicochemical properties, biocompatibility, antibacterial effects, sufficient osteoinductive capability, and sustained EGCG release over one week. 70% of the defect area was repaired with the help of the EGCG-loaded membrane, approximately 1.5-fold improvement over the control group in 8 weeks. In conclusion, these membranes are promising candidates for guided bone regeneration. Graphical abstract: Image 1 Highlights: Unstable compound, epigallocatechin gallate was successfully encapsulated within the core of nanofiber. The physicochemical and biological properties of the fabricated scaffold was extensively characterized. The scaffold turned out to be antibacterial with osteoinductive capability. The membrane exhibited promising bone regenerative capability established through stablishing rabbit calvarial defect model.